A118 FECAL CALPROTECTIN COMPLETION RATES AMONG PATIENTS WITH INFLAMMATORY BOWEL DISEASE - Bergeron, F (J Can Assoc Gastroenterol, 2019)
BACKGROUND: Fecal Calprotectin (FC) is a biomarker that has been shown to be sensitive and specific for mucosal inflammation in Inflammatory Bowel Disease (IBD). FC is useful to monitor disease activity and response to therapy in patients with IBD. Unfortunately, several factors contribute to a fairly low return rate of FC tests. AIMS: The current study aimed to determine the return rate of FC tests for patients with IBD in a clinical care setting and to assess whether there were any factors associated with a successful completion of the test. METHODS: We conducted a retrospective review of IBD patients at the Pacific Gastroenterology Associates, a tertiary, outpatient care center in Vancouver, British Columbia, Canada. All patients who were enrolled in a patient support program for the purposes of administering biologic drug treatment for their IBD and who were requested to have FC testing performed between January 2017 and September 2018 were included. Enrolled patient records were reviewed for demographic data, disease characteristics, current biologic medication, FC completion, and FC results. Univariate regression was used to identify factors potentially associated with successful completion of the test and multivariate logistic regression was used to assess the independence of those variables. RESULTS: A total of 426 patients were included in the study, 60% were female, and 82% had Crohn’s disease (CD). We observed a completion rate of 87% (n=374) of FC testing kits provided through patient support program. The median time to complete the test was four weeks (IQR 2.0–6.0). Overall, 37% (n=159) patients who completed the test had a positive FC value (>250 μg/g). Patients with CD were twice as likely to complete the test as patients with ulcerative colitis (UC) (OR 2.07 [1.07–3.98] p = 0.03). The disease location did not impact the likelihood of completing the test, but on multivariate analysis, CD patients without perianal disease had higher completion rates than those with perianal disease (OR 2.79 [1.26–6.20] p = 0.012). Interestingly, patients of a physician who specializes in IBD during pregnancy, had a lower completion rate, than those belonging to physicians who do not specialize in IBD in pregnancy. (OR 2.19 [0.86–5.54] p 0.098 and OR 2.92 [1.53–5.56] p 0.001). CONCLUSIONS: We observed a higher completion rate (87%) of FC testing kit than prior studies. This may be due to the fact that the patient support programs have a coordinator who facilitates completion of the test. While no demographic characteristics were associated with completion of the FC test, CD, especially without perianal involvement, had a higher completion rate than UC. Further study is required to clarify factors that may be associated with successful completion of FC testing in order to improve patient adherence and increase the utility of FC testing for patients with IBD. FUNDING AGENCIES: None